Manajemen Konfik Pada Pasangan Pernikahan Dini Di Kecamatan Panti - Abdillah Nur Asyukuriyah; Alif Afrizal; Ani Qotus Zuhro’ Fitriana (CV. ITTC INDONESIA, 2023)
Couples marry early, it is not uncommon for conflicts to occur which then lead the couple to experience tension and differences in principles in marriage. Couples have different ways of resolving domestic conflicts. The study aims to find out how conflict management works for adolescents who marry early in Panti Jember District. This study used qualitative research methods. Data collection techniques were carried out by interviews, observation, and documentation. The research subjects were three couples who were married teenagers aged 19-21 years. The results of the study show that there are three main themes, namely the causes of conflict, forms of conflict management, and factors that influence the application of conflict management by early marriage couples. The causes of conflict include emotional maturity, stress, and conflict with partners. Furthermore, the forms of conflict management that have proven effective to be applied to these conflicts are accommodation, collaboration, and conflict avoidance. Finally, the factors that affect the ability to apply conflict management are self-introspection, establishing good communication, respect, and support from partners.